ELECTROMAGNETIC RADIATION reflection and TRANSMISSION characteristics of SHIELDING POLYESTER fabric with nanostructured FERROMAGNETIC microwire, CONTAINING COPPER CLUSTERS - O. V. Boiprav; A. A. Ahmed; L. M. Lynkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It’s obtained the change regularities of electromagnetic radiation reflection and transmission characteristics of shielding polyester fabric with nanostructured ferromagnetic microwire when copper deposited on its fibers surface from water solutions. Recommendations for the practical application of such fabric are proposed.